ALOKASI FAKTOR PRODUKSI DAN SISTEM PEMASARAN PADI ORGANIK DI KABUPATEN LAMPUNG TENGAH - Putri, Chindy Yulianti; Widjaya, Sudarma; Nikmatullah, Dewangga (Jurnal Ilmu-Ilmu Agribisnis, 2020)
This research aims to analyze the factors that affect organic rice production, determine the level of efficiency of organic rice production, find out the marketing chain of organic rice and the prospects for sustainability of the organic rice program after the assistance project was completed. The research was conducted in Central Lampung Regency on March-May 2018. The research sample consisted of 32 organic rice farmers using a census method. Data were analyzed using Cobb-Douglass production function method, frontier production function, and S-C-P (Structure, Conduct, Performance) method. The results showed that the prospect of the sustainability of the program with the SRI method was not successfully implemented and the factors that affected the organic rice production were seeds and compost fertilizer. Farmers in Central Lampung Regency from year to year have always experienced a decline in organic rice production, which has an effect on the level of farming efficiency. The value of technical efficiency obtained was 86.21% and the value of ?bi?1, so that farming has not been efficient. Organic rice at the research site was marketed from farmers to farmer groups and directly to consumers. The RPM value obtained was equal to 3.74%.Keywords: analyze, efficiency, marketing, production, organic rice